Variability in photosynthetic production of dissolved and particulate organic carbon in the North Pacific Subtropical Gyre - Viviani, Donn A.; Karl, David M.; Church, Matthew J. (Frontiers in Marine Science, 2015)
The partitioning of photosynthetically-derived organic carbon between particulate and dissolved phases has important implications for marine carbon cycling. In this study we utilized 14C-bicarbonate assimilation to quantify rates of photosynthetic production of both particulate and dissolved organic carbon (DOC) at Station ALOHA (22˚45’N, 158˚W) in the North Pacific Subtropical Gyre (NPSG). At near-monthly time scales over 5 years, we examined retention of 14C-labeled organic matter by both glass fiber filters and 0.2 µm pore size polycarbonate membrane filters that are commonly used for measurements of 14C-based plankton productivity. Use of polycarbonate filters resulted in significantly lower (averaging 60%) estimates of 14C-production compared to glass fiber filters. Coincident measurements of chlorophyll a concentrations from both 0.2 µm polycarbonate and glass fiber filters were not significantly different, suggesting the differences in 14C-productivity between these filter-types did not derive from differences in retention of photosynthetic biomass by these filters. Moreover, consistent with previous studies, results from experiments aimed at quantifying retention of organic matter by these filters suggested the difference between these two types of filters resulted from retention of DOC by glass fiber filters. We also quantified rates of 14C-DOC production to evaluate the partitioning of photosynthetic production between dissolved and particulate phases over daily to monthly time scales in this ecosystem. Unlike the strong depth-dependence observed in measurements of particulate organic carbon production, measured rates of 14C-DOC demonstrated no clear depth-dependence. On average, depth-integrated (0-75 m) rates of 14C-DOC production rates were equivalent to 18 ± 10% of the total (particulate and dissolved) productivity. Our findings indicate that in this oligotrophic ecosystem, rates of dissolved and particulate production can be temporally decoupled over daily to monthly time scales.